Experimental Verification of the Time-Fractional Diffusion of Methanol in Silica - Zhokh, Alexey A.; Strizhak, Peter E. (Journal of Applied Nonlinear Dynamics, 2026)
Experimental study of the mass transfer kinetics for methanol in mesoporous silica is presented. Analysis of the experimental data shows that there is no good correspondence between them and corresponding solutions found according to the second Fick’s law for various pores geometries of the silica. Contrary, we show a good fit of the experimental data by a solution of the time-fractional diffusion equation with proper boundary conditions that correspond to experiment. Our results support that mass transfer in silica, which is a geometrically restricted media, may exhibit anomalous features, due to the geometrical constraints associated with randomly porous structure of a solid.